Simultaneous Onset of Pediatric Systemic Lupus Erythematosus in Twin Brothers: Case Report - Raupov, Rinat K.; Suspitsin, Evgeny N.; Imelbaev, Artur I.; Kostik, Mikhail M. (Frontiers in Pediatrics, 2022)
There are hundreds of twin adult patients with systemic lupus erythematosus (SLE), but male children with SLE are rarely affected. Two monozygotic twin brothers developed SLE at the age of 11 years during 1 month. The index brother manifested with Henoch-Shonlein purpura, accompanied by ANA positivity, and later developed critical left femoral arterial stenosis with high levels of anti-dsDNA, antiphospholipid antibodies, hypocomplementemia, and Coombs-positive hemolytic anemia. At that time his twin brother had only identical autoimmune findings and developed clinical manifestation (myositis and fasciitis) a month later. Both twins had increased IFN-score and shared a heterozygous variant in the RNASEL gene. Index patients developed scalp rash and nephritis six months after their parents refused the treatment which has been lasted for one year after disease diagnostics. Conclusion: The simultaneous onset of the pediatric SLE in the male twin is a very rare situation suspected monogenic origin of the disease. Further functional studies are required to confirm the causative role of the mutation.